Immunosuppressive Drugs Affect High-Mannose/Hybrid N-Glycans on Human Allostimulated Leukocytes - Ewa Pocheć; Katarzyna Bocian; Marta Ząbczyńska; Grażyna Korczak-Kowalska; Anna Lityńska (Analytical Cellular Pathology)
N-glycosylation plays an important role in the majority of physiological and pathological processes occurring in the immune system. Alteration of the type and abundance of glycans is an element of lymphocyte differentiation; it is also common in the development of immune-mediated inflammatory diseases. The N-glycosylation process is very sensitive to different environmental agents, among them the pharmacological environment of immunosuppressive drugs. Some results show that high-mannose oligosaccharides have the ability to suppress different stages of the immune response. We evaluated the effects of cyclosporin A (CsA) and rapamycin (Rapa) on high-mannose/hybrid-type glycosylation in human leukocytes activated in a two-way mixed leukocyte reaction (MLR). CsA significantly reduced the number of leukocytes covered by high-mannose/hybrid N-glycans, and the synergistic action of CsA and Rapa led to an increase of these structures on the remaining leukocytes. This is the first study indicating that β1 and β3 integrins bearing high-mannose/hybrid structures are affected by Rapa and CsA. Rapa taken separately and together with CsA changed the expression of β1 and β3 integrins and, by regulating the protein amount, increased the oligomannose/hybrid-type N-glycosylation on the leukocyte surface. We suggest that the changes in the glycosylation profile of leukocytes may promote the development of tolerance in transplantation.